Heuristic UTD coefficients for radiowave coverage prediction in a urban scenario (2015)
This paper presents a comparison of three heuristic coefficients for the Uniform Theory of Diffraction (UTD), used to characterize the radiowave scattering in typical urban scenarios. The coefficients were implemented in a propagation model based on ray-tracing techniques based in image theory. In order to evaluate each coefficient we analyze the statistical behavior of the mean and standard deviation of the absolute errors between the estimated values and the measured data of path loss in a large number of receptor points provided in the literature. Finally, we show the path loss prediction for each UTD coefficients proposed.